2013
DOI: 10.17816/kmj2186
|View full text |Cite
|
Sign up to set email alerts
|

Health of the migrants as a social problem

Abstract: An analysis of law and enactments, mass-media publications, statistics and healthcare institutions documents, interviews with experts and diasporas leaders was performed to assess the contemporary international and Russian approaches to migrants health and to reveal the features of healthcare services provided for migrants in the Republic of Tatarstan. A social risk connected to migrants health is associated with increase of number of migrant workers with ailments, returning to their communities for treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The ambiguities, and corruption, in the labor system, means that they endure low paid work, often short-term and without any form of contract (see also Heusala and Aitamurto, 2016; Urinboyev and Polese, 2016), and even become victims of human trafficking (Buckley, 2018). Before the patent reform, survey of migrants conducted in Tatarstan, showed that around 55 percent work fully informally, with a similar figure obtained from interviewees in Moscow (Kuznetsova and Muchyaramova, 2014). As result of this informality in Tatarstan, 10 percent regularly received lower wages than agreed and over a quarter this had happened to them on numerous occasions.…”
Section: Between Being Undocumented and “Documented”: Issues Around Informalitymentioning
confidence: 53%
“…The ambiguities, and corruption, in the labor system, means that they endure low paid work, often short-term and without any form of contract (see also Heusala and Aitamurto, 2016; Urinboyev and Polese, 2016), and even become victims of human trafficking (Buckley, 2018). Before the patent reform, survey of migrants conducted in Tatarstan, showed that around 55 percent work fully informally, with a similar figure obtained from interviewees in Moscow (Kuznetsova and Muchyaramova, 2014). As result of this informality in Tatarstan, 10 percent regularly received lower wages than agreed and over a quarter this had happened to them on numerous occasions.…”
Section: Between Being Undocumented and “Documented”: Issues Around Informalitymentioning
confidence: 53%
“…This issue is particularly relevant as extensive foreign labour migration is a relatively recent phenomenon in Russia. As a result, necessary legal provisions and social programmes aimed at both documented and undocumented migrants are often lacking (Kuznetsova and Mukharyamova, : 370). This situation is exacerbated by widespread discriminatory practices towards migrants by the host society and by public institutions.…”
Section: Introductionmentioning
confidence: 99%